An Analysis of the Relationship between Brain Waves in Electroencephalography (EEG) and Concentration Meditation Practice in Theravāda Buddhism - Klunsupha, Nopporn (Journal of International Buddhist Studies, 2023)
Nowadays in Western countries, there is much interest in studies of Buddhist meditation practice. This article is focused on an analysis of the relationship between brainwaves in electroencephalography (EEG) and concentration practices in Theravāda Buddhism. The following are the findings: meditation has a good effect on the brain. Despite the fact that we can detect these good effects by several methods, one of these methods (EEG measurement) shows that deep meditation activates slow brainwaves, and we can use meditation in many ways to improve emotional & physical health. Based on the findings in this analysis, the more deep concentration, the more brain synchronization occurs, and the slower are the brainwaves. As a result, the body and the brain can rest. Therefore, our findings indicate that meditation can be used to release stress, anxiety and depression. It can also heal diseases and improve some symptoms thereby contributing to disseminate concentration practices in Theravāda Buddhism in modern science in order to create love, happiness and wisdom to build the world peace.